COMPARATIVE STUDY OF LEXICAL MEANS RELATED TO WEDDING IN UZBEKI AND GERMAN LANGUAGES - Zilola Pazilova (Western European Studies, 2024)
This article discusses Uzbek and German wedding ceremonies, how they are conducted, and place names associated with the wedding
Keywords: property; bride drop off; dowry; curtain